Rural migration and regional development: The example of Indonesia - Karl Fasbender (Intereconomics, 1989)
Regional disequilibria in the distribution of population lead in many developing countries to migration flows which cannot always be equated with flight from the land or drift to the cities. In diverse countries rural-rural migration is even supported by the state. This rural migration leaves a decisive mark not only on the regional development of the areas from which emigration takes place but also on the absorbing areas. The following article examines the costs and benefits for both.
Keywords: 330; Development Strategy